2008
DOI: 10.4081/jlimnol.2008.75
|View full text |Cite
|
Sign up to set email alerts
|

The water chemistry of some shallow lakes in Northern Patagonia and their nitrogen status in comparison with remote lakes in different regions of the globe

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 63 publications
5
60
1
1
Order By: Relevance
“…It is reasonable to expect that nitrogen deposition in the high mountain areas of the Julian Alps would be higher than that in Rateče due to: i) precipitation amounts approximately twice as high (Kastelec, 1999), and ii) higher elevation and upwind direction that would change the composition of precipitation and thus could be above the critical threshold and closer to the value that Rogora et al (2006) reported for the Central-Southern Alps (14-16 kg N ha -1 yr -1 ). Furthermore, it seems that nitrogen deposition in the whole southern rim of the European Alps is considerably higher than in some other mountain or remote areas of the world (Rogora et al, 2008), e.g. Northern Patagonia in the Andes, Svalbard islands, the Khumbu-Himal region of the Himalayas and the Serra da Estrela in continental Portugal, where depositions up to 7 kg N ha -1 yr -1 were observed.…”
Section: Atmospheric Nitrogen Deposition and Its Impact On Slovenian mentioning
confidence: 94%
“…It is reasonable to expect that nitrogen deposition in the high mountain areas of the Julian Alps would be higher than that in Rateče due to: i) precipitation amounts approximately twice as high (Kastelec, 1999), and ii) higher elevation and upwind direction that would change the composition of precipitation and thus could be above the critical threshold and closer to the value that Rogora et al (2006) reported for the Central-Southern Alps (14-16 kg N ha -1 yr -1 ). Furthermore, it seems that nitrogen deposition in the whole southern rim of the European Alps is considerably higher than in some other mountain or remote areas of the world (Rogora et al, 2008), e.g. Northern Patagonia in the Andes, Svalbard islands, the Khumbu-Himal region of the Himalayas and the Serra da Estrela in continental Portugal, where depositions up to 7 kg N ha -1 yr -1 were observed.…”
Section: Atmospheric Nitrogen Deposition and Its Impact On Slovenian mentioning
confidence: 94%
“…Much of this effect of altitude on species distributions has been attributed to the indirect effects that altitude has via its influences on other habitat characteristics. For example, in the lakes of Patagonia (southern South America), Rogora et al (2008) demonstrated negative correlations between conductivity and altitude between 679 and 1466 m a.s.l., suggesting lower conductivities (referring to low salinity) in waters are coupled with increasing altitude. Consistent with this rationale, Reeves et al (2007) found that altitude affected water depth, water chemistry, temperature and conductivity, and that as a result groundwater ostracods were restricted to midaltitude locations in the Pilbara region of northwestern Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Like rivers, the biological communities of alpine lakes can act as sensitive indicators of 5 climate change, as even small perturbations of their natural equilibrium may cause detectable 6 responses (Rogora et al, 2008). Hence, the identification of indicator taxa for monitoring 7 glacier retreat in lake environments is feasible.…”
Section: Introductionmentioning
confidence: 99%